POST - CAPTURE EVALUATION OF Aotus vociferans and Aotus nancymae IN PERUVIAN AMAZON FORESTS - AQUINO-Y., Rolando (1992)
In order to evaluate the effects of the partial removal of the Aotus vociferan and A. nancymae populations, we made captures in areas corresponding to the lowland forests of the Napo and Amazon river basins. In the first capture of A. vociferans executed in 1986 in the Tamboryacu River, 35.5% of the population was removed and in 1989 in the Santa Maria River 55% of the population was removed. During the 1991 evaluation, in the Tamboryacu River the increase of the remaining population reached 144.0% and 93.0% of the 1986 pre-capture level, while in the Santa María River, the increase reached 12.5% of the remaining population and 50% of the 1989 pre-capture level. In reference to A. nancymae, during the first capture executed in 1989 in the Tahuayo river, 50.0% of the population was removed and in the Yanayacu stream, 59.0% of the population was removed. Two years later, the increase in the Tahuayo River was 10.0% of the remaining population, reaching 48.0% of the pre-capture level of 1989, while in the Yanayacu Creek the increase was 55.0% of the remaining population and 61.0% of the pre-capture level of 1989. The low level of recovery of the A. nancymae population in the Tahuayo River is related to intense subsistence hunting and to a lesser degree to deforestation. In the Santa María River, it is only due to deforestation for agricultural purposes, which in 1991 reached 51.0% of the total area. After the captures, births and immigrations in both A. vociferans and A. nancymae contributed to the repopulation in the affected areas, the proportions of which could not be specified.